FRAKSI ETIL ASETAT SPONS Stylissa carteri MENURUNKAN VIABILITAS SEL KANKER PAYUDARA TIPE HER2+ RESISTEN TRASTUZUMAB - Julia Nur Jannah; Pandji Irani Fianza; Tenny Putri; Muhammad Hasan Bashari (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: HER2+ breast cancer is a very aggressive type of breast cancer. Although trastuzumab, specifically targeted for HER2, has been used for breast cancer treatments, some patients become resistant to trastuzumab. A marine sponge is one of the potential sources of anticancer agents. One of marine sponges commonly found in Indonesia is Stylissa carteri, but it has not been explored extensively.Objective: This study aimed to identify cytotoxic effects of the ethyl acetate fraction of Stylissa carteri on HCC-1954, HER2+ trastuzumab-resistant breast cancer cells, by assessing cell viability and determining IC50 value.Methods: This study was an experimental in vitro study conducted in The Cell Culture Laboratory, Faculty of Medicine Universitas Padjadjaran on February 2018 to June 2018. The Stylissa carteri was collected from Pramuka Island, Kepulauan Seribu National Park Jakarta. HCC-1954 cells were treated by serial concentration of fractions and were incubated for 72 hours. Cell viability were observed under a microscope and analysed with MTT assay. The IC50 value was also determined by using four parametric logistic regression (4PL) method by Sigmaplot version 12.0. Result: Data of this study showed descent of cell viability significantly when exposing the ethyl acetate fraction of Stylissa carteri. There was a decrease of 49% cell viability in 10 µg/ml of the ethyl acetate fraction of Stylissa carteri. The estimated IC50 value was 9.25 µg/ml.Conclusion: This result indicated that the ethyl acetate fraction of Stylissa carteri has cytotoxic effects on HER2+ trastuzumab-resistant breast cancer cells.